Empowering Women in Indonesia’s Tourism Villages: The Role of MSMEs in Economic Development - Sirad, Dini Anggraeni; Widiastini, Ni Made Ary; Karta, Ni Luh Putu Agustini (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
The rapid increase in women's employment opportunities in Indonesia’s tourism sector, particularly in the informal sector, highlights their crucial role in the economic development of tourism villages. This study examines women's participation in the hotel industry and their adaptation and innovation in micro, small, and medium enterprises (MSMEs) across Bali, Banyuwangi, Banten, and Jogja. Using participant observation, in-depth interviews, and documentation studies, the research finds that women play strategic roles as business managers, tourism drivers, and cultural preservers. However, challenges such as limited capital access and market constraints persist, influenced by resource availability, infrastructure, local culture, and market potential. Despite these barriers, women leverage government and private sector training programs to enhance their skills and overcome obstacles. Strengthening women’s empowerment in tourism villages is essential for sustaining local economic growth and improving community welfare.